Family Nursing Care for Pregnant Women with Hypertension in The Working Area of The Lapai Public Health Center, Padang City - Sidik, Alivia; N. Rachmadanur; Tasman; Astuti, Verra Widhi; Amri, Lola Felnanda (POLTEKKES KEMENKES PADANG, 2024)
Pregnant women are at risk of experiencing health problems with increasing age, one of which is the risk of hypertension where systolic blood pressure is above 140 mmHg and diastolic blood pressure is above 90 mmHg or more. The aim of this research is to describe family nursing care for pregnant women with hypertension. Descriptive research method with a case study approach. The research was conducted at the Lapai Health Center, Padang City. The research population consisted of 4 people. Sampling used the Simple Random Sampling technique. The data collection instrument is a family nursing care assessment format. Data were analyzed by comparing research results based on theory and previous research. The results of the research showed that the client complained that she felt a headache, weak, and her body got tired easily. Data was collected using interviews, observations, physical examinations and documentation studies of swelling. In her first pregnancy, she also felt the same complaint. The client's family said the client often consumed salty foods and rarely consumed vegetables. The problems found were ineffective peripheral perfusion, risk of injury to the fetus, and anxiety. Nursing implementation carried out health education for pregnant women with hypertension, foot soaking technique therapy with warm water and lemongrass, carrying out deep breathing and guided imagination techniques, modifying a comfortable and safe environment for pregnant women with hypertension, and introduction of the nearest health facility services. Nursing evaluation found that some problems were resolved. It was concluded that the client had understood the education about hypertension in pregnancy, the anxiety felt had been resolved, the client was able to do the foot soaking technique with warm water and lemongrass. It is recommended that it can help in developing community health center programs in providing nursing care.